2016
DOI: 10.1166/jnn.2016.12231
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Amination via Cycloaddition of Graphene for Use in a Glucose Sensor

Abstract: Graphene was chemically aminated via cycloaddition. Aziridine-ring linkages were formed by covalently modifying the C-C double bonds in graphene. The aminated graphene presents an enhanced hydrophilicity, the contact angle with water decreases from 80.5 degrees to 58.5 degrees. And the conductivity of aminated graphene exhibits exponential decay as the reaction time increase. If the reaction time is 90 min, the resistance of aminated graphene was increased from -32 Ω to -2744 Ω. Because the amino group has goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…After the GO treatment, the characteristic absorption bands at 2970-3700 cm −1 , 1365 cm −1 , 1220 cm −1 and 980 cm −1 related to the interlayer water and oxygen functionalities diminish 38 . At the same time, new doublet at 3422 cm −1 and 3306 cm −1 along with peaks at 1560 cm −1 , 1260 cm −1 and 795 cm −1 corresponding to N-H stretching of primary amines, N-H bending of primary amines, C-N stretching and N-H wag, respectively 39,40 , appear and become dominant. The additional bands at 1404 cm −1 2920 cm −1 attributed to C-H/C-H 2 vibrations are due to the isopropyl alcohol molecules retained after the sample preparation.…”
Section: Resultsmentioning
confidence: 94%
“…After the GO treatment, the characteristic absorption bands at 2970-3700 cm −1 , 1365 cm −1 , 1220 cm −1 and 980 cm −1 related to the interlayer water and oxygen functionalities diminish 38 . At the same time, new doublet at 3422 cm −1 and 3306 cm −1 along with peaks at 1560 cm −1 , 1260 cm −1 and 795 cm −1 corresponding to N-H stretching of primary amines, N-H bending of primary amines, C-N stretching and N-H wag, respectively 39,40 , appear and become dominant. The additional bands at 1404 cm −1 2920 cm −1 attributed to C-H/C-H 2 vibrations are due to the isopropyl alcohol molecules retained after the sample preparation.…”
Section: Resultsmentioning
confidence: 94%
“…Amine functionalization of graphene has been pursued for various applications in energy storage, 24,25 as drug-delivery vehicles, 26 transparent electrodes for polymer solar cells, 27 sensors for aqueous contaminants 28 or biomolecules 29 and composites. 30,31 The majority of these studies have been carried out directly on the graphite oxide, using different reactants and extending the initial work by Bourlinos et al 32 However, this strategy retains the insulating character of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Amine functionalization of graphene has been pursued for various applications in energy storage, , as drug-delivery vehicles, transparent electrodes for polymer solar cells, sensors for aqueous contaminants, or biomolecules and composites. , The majority of these studies have been carried out directly on the graphite oxide, using different reactants and extending the initial work by Bourlinos et al However, this strategy retains the insulating character of GO. Amination of graphene or reduced graphene oxide has received less consideration since specific equipment, hazardous chemicals, or a large number of steps are required. ,,,, For instance, Bittolo Bon et al reported the amination of thermally reduced graphene oxide (TRGO) via plasma activation.…”
Section: Introductionmentioning
confidence: 99%
“…A maleimide derivative was also employed by Yu et al to achieve an atomic-scale controlled and ordered modification of Cu(111)/EG. [61] The reaction control was obtained by two sequentialsteps: In the first step, the maleimide derivative is sublimated onto the single-layer graphene forming an SiO 2 /CVDG 4-Azidoaniline 0.7 [a] p-doped [64] [a] This value was calculated considering the data reported in Ref. [64].…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%